RELATIONSHIP ILMU (Science) dan AGAMA (Religion) - Fatonah, Kuni; Sumarno, Sumarno (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2021)
At the beginning of his creation, humans are just creatures who do not know anything and therefore humans need a guide for their way of life. Humans need guidelines so that their lives are safe in this world and in the hereafter. The guideline for humans is religion. Religion is a guide to life that covers all aspects of human beings, including science. Science and religion are two things that occupy an important position in this world. Both are interesting objects to discuss. The position of the two disciplines gives each other positive values ​​in answering the problems of life and humanity. . Humans also experience and witness problems related to the dimensions of the mysteries in life that cannot be solved except by referring to religion, so that the existence of religion, apart from being a belief system that requires truth, is also a practical action against the application of belief (faith). whose truth has been recognized through a methodology that has been agreed upon. This research method is to use review articles from several sources, and aims to find out how the relationship between science and religion.